Evaluation Of Natural And Synthetic Fibres Reinforced Polyester Composites Subjected To Adhesive And Abrasive Wear Modes - Yousif, Belal F. (2008)
Evaluation Of Natural And Synthetic Fibres Reinforced Polyester Composites Subjected To Adhesive And Abrasive Wear Modes